The Compensation to Stop Agricultural Field Burning From Tourism: Evidence From Luangprabang, Laos - Sisouphanthong, Viriyasack (International Journal of Multidisciplinary in Management and Tourism, 2020)
This paper tackles the impact of smoke from agricultural field burning on tourism using data of LPB, the world heritage site, in 2011. A statistical test, the contingent valuation method, and simple cost of working in agricultural farm are used for the consciousness, the willingness to pay, and the cost for not to burn. 284 firms and 280 households are interviewed in 2011 to data use. The empirical results showed that people in tourism area concern about the smoke problem. The business with potential to earn more from tourism as well as firms locate in main tourism area is likely to concern more on the smoke problem. The WTP of business and household to stop the smoke is 1,578 millions kip (197,342 US dollars) annually, and the cost for farmer to clear their field without using fire is 620 millions kip (77,487 US dollars) annually.